Integrative Analysis of Biomarkers and Mechanisms in Adamantinomatous Craniopharyngioma - Lin, Da; Zhao, Wenyue; Yang, Jun; Wang, Hao; Zhang, Hongbing (Frontiers in Genetics, 2022)
Craniopharyngioma is a benign tumor, and the predominant treatment methods are surgical resection and radiotherapy. However, both treatments may lead to complex complications, seriously affecting patients’ survival rate and quality of life. Adamantinomatous craniopharyngioma (ACP), as one of the histological subtypes of craniopharyngioma, is associated with a high incidence and poor prognosis, and there is a gap in the targeted therapy of immune-related genes for ACP. In this study, two gene expression profiles of ACP, namely GSE68015 and GSE94349, were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) were identified by the Limma package, and 271 differentially expressed immune-related genes (DEIRGs) were obtained from the Immport database. The gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Set Enrichment Analysis (GSEA) were performed for annotation, visualization, and integrated discovery. Five hub genes, including CXCL6, CXCL10, CXCL11, CXCL13, and SAA1, were screened out through protein-protein interaction (PPI) network interaction construction. Two diagnostic markers, namely S100A2 and SDC1 (both of which have the Area Under Curve value of 1), were screened by the machine learning algorithm. CIBERSORT analysis showed that M2 macrophages, activated NK cells, and gamma delta T cells had higher abundance in ACP infiltration, while CD8+ T cells, regulatory T cells, and Neutrophils had less abundance in ACP infiltration. The expression of gamma delta T cells was positively correlated with CXCL6, S100A2, SDC1, and SAA1, while CD8+ T cells expression was negatively correlated with CXCL6, S100A2, SDC1, and CXCL10. ACP with high CXCL6 showed remarkable drug sensitivity to Pentostatin and Wortmannin via CellMiner database analysis. Our results deepened the understanding of the molecular immune mechanism in ACP and provided potential biomarkers for the precise targeted therapy for ACP.